The effect of knowledge absorptive capacity on social ventures' performance - Youngkeun Choi; Sug-in Chang; Sung-Jun Youn (Cogent Business & Management, 2021)
This study explores the complementary role of acquisition/assimilation and transformation/exploitation in the absorptive capacity in the perspective of knowledge absorptive capacity. For this, depending on human capital and resource-based view, this study pays attention to the interaction effect of social entrepreneurs' prior experiences and the partnership types of their social ventures on their social ventures' performance. In the Korean context, social enterprises have another function to provide jobs and increase employment rates in a time of low economic growth and economic inequality. Given this situation, it is necessary that researchers investigate what human capitals of social entrepreneurs are helpful to obtain better social and commercial performance and what types of the partnership may have moderating effects on the relationship between the human capitals of social entrepreneurs and the social and commercial performance of social ventures. In the results, first, social entrepreneurs' prior social experience is positively related to the social performance of their social ventures. Second, social entrepreneurs' prior commercial experience is positively related to the commercial performance of their social ventures. Third, partnerships with non-profit organizations enhance the positive relationship between social entrepreneurs' prior social experience and their social venture's social performance. Finally, partnerships with for-profit organizations enhance the positive relationship between social entrepreneurs' prior commercial experience and their social venture's commercial performance.
Keywords: 650; social venture; knowledge absorptive capacity; human capital theory; resourcebased view